Multi-modal analysis of courtship behaviour in the old world leishmaniasis vector Phlebotomus argentipes. - Daniel P Bray; Khatijah Yaman; Beryl A Underhilll; Fraser Mitchell; Victoria Carter; James G C Hamilton (PLoS Neglected Tropical Diseases)
Background The sand fly Phlebotomus argentipes is arguably the most important vector of leishmaniasis worldwide. As there is no vaccine against the parasites that cause leishmaniasis, disease prevention focuses on control of the insect vector. Understanding reproductive behaviour will be essential to controlling populations of P. argentipes, and developing new strategies for reducing leishmaniasis transmission. Through statistical analysis of male-female interactions, this study provides a detailed description of P. argentipes courtship, and behaviours critical to mating success are highlighted. The potential for a role of cuticular hydrocarbons in P. argentipes courtship is also investigated, by comparing chemicals extracted from the surface of male and female flies. Principal findings P. argentipes courtship shared many similarities with that of both Phlebotomus papatasi and the New World leishmaniasis vector Lutzomyia longipalpis. Male wing-flapping while approaching the female during courtship predicted mating success, and touching between males and females was a common and frequent occurrence. Both sexes were able to reject a potential partner. Significant differences were found in the profile of chemicals extracted from the surface of males and females. Results of GC analysis indicate that female extracts contained a number of peaks with relatively short retention times not present in males. Extracts from males had higher peaks for chemicals with relatively long retention times. Conclusions The importance of male approach flapping suggests that production of audio signals through wing beating, or dispersal of sex pheromones, are important to mating in this species. Frequent touching as a means of communication, and the differences in the chemical profiles extracted from males and females, may also indicate a role for cuticular hydrocarbons in P. argentipes courtship. Comparing characteristics of successful and unsuccessful mates could aid in identifying the modality of signals involved in P. argentipes courtship, and their potential for use in developing new strategies for vector control.